Studies on the Distributional and Phenological Aspects of Calamus L. in Karnataka - Kumar, H. N. Krishna; Ramaswamy, S. N. (Indian Forester, 2004)
Results of a study on the distribution, natural habitats and phenological observations are presented. The natural habitats of rattans in the Western Ghats of Kar'nataka in Belgaum, Chikmagalore, Coorg, Hassan. North Canara, Shimoga and South Canara districts are studied. In general, the flowering is from October to January and the fruiting season is from March to July. The associated trees with rattans are listed. The effects of destruction of forests in the Western Ghats in the name of development is discussed. A sustainable utilization of rattans for the present and future human use in Karnataka and the conservation of their native habitats with the associated biodiversity is strongly pleaded.